THE MESSAGE OF DAKWAH IN THE NOVEL HATI SUHITA BY KHILMA ANIS AND THE NOVEL TWO BARISTA BY NAJHATI SHARMA - Rif’atul Maula (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
Novel is a literary work which is also known as fiction. Therefore, the notion of fiction also applies to the novel, which is a result of dialogue, contemplation, and the author's reaction to the environment and life. Each writer has a message that is implied in each of his works, one of which is as a distributor of da'wah messages. In this study, the researcher chose the novel Hati Suhita by Khilma Anis compared to the novel Dua Barista by Najhati Sharma. Because these two novels are the work of writers who were born in Islamic boarding schools. This research uses descriptive qualitative method. The results of this study indicate that there are similarities and differences in the message of da'wah in the novel Hati Suhita by Khilma Anis and the novel Dua Barista by Najhati Sharma.